2018
DOI: 10.1097/iae.0000000000001668
|View full text |Cite
|
Sign up to set email alerts
|

Macular Edema After Cataract Surgery in Eyes With Preoperative Retinal Vein Occlusion

Abstract: Pseudophakic macular edema frequently developed after phacoemulsification cataract surgery in patients with a history of retinal vein occlusion. The risk of PME further increased when the patient had undergone macular edema treatment and had a higher prevalence of intravitreal injection treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Chu et al reported patients with RVO were 4.47 times more likely to develop PCMO. Previous treatment for macular oedema, and a higher number of prior intravitreal injections of bevacizumab and/or steroids were also associated with an increased risk of developing PCMO …”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chu et al reported patients with RVO were 4.47 times more likely to develop PCMO. Previous treatment for macular oedema, and a higher number of prior intravitreal injections of bevacizumab and/or steroids were also associated with an increased risk of developing PCMO …”
Section: Risk Factorsmentioning
confidence: 99%
“…Previous treatment for macular oedema, and a higher number of prior intravitreal injections of bevacizumab and/or steroids were also associated with an increased risk of developing PCMO. 23 Posterior capsule rupture during cataract surgery is a potentially serious intraoperative complication that is strongly associated with an increased risk of PCMO. Chu et al 12 reported a relative risk of 2.61 in eyes with posterior capsule rupture-with or without vitreous loss.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…57 The effect of intravitreal anti-VEGF injections, such as bevacizumab and aflibercept, remains controversial as recent case series have shown variable results in treatment of PCME. [58][59][60][61] A recent case report on the use of intravitreal ketorolac, found no significant effect of visual acuity and macular thickness.…”
Section: Treatmentmentioning
confidence: 99%
“…3,4,59,60 The optimal strategy before, during and after cataract surgery should be tailored to the needs of the individual patient. Although the ESCRS PREMED study investigated the optimal prevention in patients with and without DM, this study did not investigate patients with other risk factors for developing CME after cataract surgery.…”
Section: Prevention Of Cystoid Macular Edema In Other High-risk Patientsmentioning
confidence: 99%